Stability of PRESAGE® dosimeter for end-to-end radiotherapy dosimetry audit and dose delivery - Mohyedin, Muhammad Zamir; Zin, Hafiz Mohd; Ung, Ngie Min; Bradley, David A.; Abdul Rahman, Ahmad Taufek (Elsevier Ltd, 2025)
The stability of commercially available PRESAGE® was evaluated for use in complex radiotherapy dose delivery and audit. The dose-response of PRESAGE® under room temperature, low temperature and exposure to visible light was investigated. The photon energy and dose rate dependence of the PRESAGE® were also investigated. It shows a different response under different temperatures. It was demonstrated that this batch of PRESAGE® shows decreased optical density (OD) over time instead of increased OD like a common PRESAGE®. Additionally, the OD of PRESAGE® decreases more slowly which is 0.1 % each hour under low temperature. PRESAGE® also quickly returned to its original state within 48 h post-irradiation under room temperature which the OD decreased by 2.06 % each hour. Upon its return to its original state, the PRESAGE® was able to be reused again with the dose-response reproducibility of more than 99 %. This study also shows that the PRESAGE® is highly sensitive to the visible light radiated by the common fluorescent lamp. The longer the exposure, the higher the optical density within the PRESAGE® which on average, the OD increased by 21.13 % each hour of exposure. The PRESAGE® shows a small dependence of energy with the linearity difference of 5.22 % and shows the independence of dose rate with a variation of less than 5 %.